An Applied Anatomical Study of the Ethmoidal Arteries: Computed Tomographic and Direct Measurements in Human Cadavers. Issue 1 (January 2018) - Felding, Ulrik Ascanius; Karnov, Kirstine; Clemmensen, Anne; Thomsen, Carsten; Darvann, Tron A.; Buchwald, Christian von; Tranum-Jensen, Jørgen
Abstract : Abstract: Computed tomography (CT) images have been used in very few studies on distances to the ethmoidal arteries in the orbit. Most other studies have included direct measurements on cadavers and frequently quote the 24–12–6 mm rule to describe distances from the anterior lacrimal crest to the anterior and posterior ethmoidal foramina (AEF and PEF), optic canal (OC), respectively. However, the large interindividual variation of distances renders absolute values less applicable in a clinical setting. Preoperative measurements on CT images may provide more precise distances than absolute rules and thus lead to safer orbital surgery. The authors hypothesize that the distances to the ethmoidal arteries and the length of the medial wall are positively correlated and that measurements of the distances from the posterior lacrimal crest (PLC) on CT images are feasible with a low intra- and interobserver variability. Fifty intact orbits from 25 Caucasian cadavers were exenterated and examined. In additional, high-resolution CT scans of 48 orbits from 24 other Caucasian nonexenterated cadavers were examined. Distances were measured from 4 different anterior landmarks to the AEF and PEF and the OC. Distances from the most anterior landmarks to the arteries were positively correlated with the length of the medial wall. Measurements of the distances from the PLC to the ethmoidal arteries on CT images were feasible with a low intra- and interobserver variability. In conclusion, iatrogenic damage to the ethmoidal arteries in the orbit may be best avoided by using CT measurements in presurgical planning.